Hydration Is More Important Than Exogenous Carbohydrate Intake During Push-to-the-Finish Cycle Exercise in the Heat - Berry, Craig W.; Wolf, S. Tony; Cottle, Rachel M.; Kenney, W. Larry (Frontiers in Sports and Active Living, 2021)
Dehydration ≥2% loss of body mass is associated with reductions in performance capacity, and carbohydrate (CHO)-electrolyte solutions (CES) are often recommended to prevent dehydration and provide a source of exogenous carbohydrate during exercise. It is also well established that performance capacity in the heat is diminished compared to cooler conditions, a response attributable to greater cardiovascular strain caused by high skin and core temperatures. Because hydration status, environmental conditions, and carbohydrate availability interact to influence performance capacity, we sought to determine how these factors affect push-to-the-finish cycling performance. Ten young trained cyclists exercised at a moderate intensity (2.5 W·kg-1) in a hot-dry condition (40C, 20% relative humidity (RH)) until dehydration of ~2% body mass. Subjects then consumed either no fluid (NF) or enough fluid (water, WAT; Gatorade®, GAT; or GoodSport™, GS) to replace 75% of lost body mass over 30 min. After a 30-min light-intensity warm-up (1.5 W·kg-1) in a 35C, 20% RH environment, subjects then completed a 120-kJ time trial (TT). TT time-to-completion, absolute power, and relative power were significantly improved in WAT (535±214sec, 259±99W, 3.3±0.9W·kg-1), GAT (539±226sec, 260±110W, 3.3±1.0W·kg-1), and GS (534±238sec, 262± 105W, 3.4±1.0W·kg-1) compared to NF (631±310sec, 229±96W, 3.0±0.9W·kg-1) all p<0.01) with no differences between WAT, GAT, and GS, suggesting that hydration is more important than carbohydrate availability during exercise in the heat. A subset of 4 subjects returned to the laboratory to repeat the WAT, GAT, and GS treatments to determine if between-beverage differences in time-trial performance were evident with a longer TT in thermoneutral conditions. Following dehydration, the ambient conditions in the environmental chamber were reduced to 21 C and 20% RH and subjects completed a 250-kJ TT. All 4 subjects improved TT performance in the GS trial (919 ± 353 sec, 300 ± 100 W, 3.61 ± 0.86 W·kg-1) compared to WAT (960±376sec, 283±91W, 3.43±0.83W·kg-1), while 3 subjects improved TT performance in the GAT trial (946±365sec, 293±103W, 3.60±0.97W·kg-1) compared to WAT, highlighting the importance of carbohydrate availability in cooler conditions as the length of a push-to-the-finish cycling task increases.